The Implementation of Multi-literacy of Literature Based on Mother Tongue Model in Reading Historical Narrative Text to The Elementary Students’ Higher Order Thinking Skill - Awalia, Evita Meylani; Rahman, Rahman; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
High order thinking skill is a sign of intelligence that is needed the most in 21st century education. Meanwhile, the result of the research in real life like PISA , shows that students‟ thinking ability is still categorized to „low‟. This research is aimed to know the students‟ high order thinking skill trough multi-literacy of mother tongue based model. Through literature study method, researcher find out that: (1) the use of multi-literacy model can improve the students‟ higher order thinking skill; (2) the syntax of multi-literacy based on mother tongue model; (3) benefit and minus of multi-literacy based on mother tongue model